SWIMMING STYLES IN JURASSIC ICHTHYOSAURS - Buchholtz E.A. (My University, 2001)
Postcranial axial anatomy of six Jurassic ichthyosaurs is described and used to define a generalized pattern of regional anatomy with four structural units (neck, trunk, tail stock, fluke). Functional interpretation of each unit predicts a generalized swimming mode that used a laterally compressed, laterally oscillating caudal fluke as the propulsive organ. Fluke displacement was accomplished by the undulation of a dorsoventrally compressed posterior tail stock acting on a stabilized anterior tail stock. The trunk was largely uninvolved in locomotion. Osteological predictors of postcranial flexibility in living aquatic axial locomotors are reviewed and used to identify the existence of a range of swimming styles within this generalized pattern among surveyed ichthyosaurs.
Keywords: Jurassic; ichthyosaurs; Mesozoic::Jurassic; Мезозой::Юрская